Social Capital Capacity as Prediction of Dengue Control - Heru Subaris; Subiyanto Subiyanto; Drajat Tri Kartono; Eny Lestary (Intelektual Pustaka Media Utama, 2016)
The program of elimination of mosquito breeding places is still low since there is no public participation effort in vector control. Social capital is key factor for sustaining any health programs implemented. This study was aimed to analyze the effectiveness of social capital impact on participation and environmental based dengue prevention programs. Study design was cross sectional. Population study was community around Bantul district. Sample was collected as 600 house hold devide on two categories endemic and potential areas. Data was collected with interviews and observation. Data were analyzed with person corelation, confirmatory analyzed and path way analyzed. There were significantly relationships between social capital and family perseption, disease perception, individual perception, environment perception and larva density p < 0,05. Relationship between perception of counselling and family perception, dengue programs and family perception p < 0,05, and the strongest factor is environment participation (r=0.296). Based on the path analysis for potential areas, social capital was effectively for increased larvae free index through family perception. Theoretically, model for social capital is more efficient in increasing the number of free larvae index through community environment participation. In potential areas, social capital is concluded to be more effectively increase of larva index through participation of individuals. In endemic areas, that dengue programs increase larva index more effectively, compared with social capital does. Strengthening of social capital is important because it effectively the coverage of larva index through environment participation both areas.